2023
DOI: 10.1177/26318318231153984
|View full text |Cite
|
Sign up to set email alerts
|

Pornography and Its Impact on Adolescent/Teenage Sexuality

Abstract: Adolescents/Teenagers are exposed to pornography due to a variety of factors and it is accepted as a process of sexual exploration/normal development of sexuality. However, early exposure to pornography and unregulated/excess exposure to pornography during the formative years of adolescence has been seen to have various long-term deleterious effects on sexual maturation, sexual behavior, Internet addiction, and overall personality development. To safeguard the growing minds of the teens from the harmful effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
1
1
0
2
Order By: Relevance
“…On this point, the literature indicates that early sexual experience among adolescents occurs in the context of sexual coercion and violence [1, 13, 67]. This study also revealed that a high frequency of watching pornographic films was associated with penetrative sexual experience, which is consistent with previous studies indicating that exposure to pornography may have harmful effects on sexual maturation and behaviours in adolescents [17, 68, 69] and that first sex was associated with exposure to pornography [7072]. In addition, another study involving adolescents aged 10-19 years in rural eastern Uganda found that watching sexually explicit films was associated with ever having sexual intercourse [73].…”
Section: Discussionsupporting
confidence: 90%
“…On this point, the literature indicates that early sexual experience among adolescents occurs in the context of sexual coercion and violence [1, 13, 67]. This study also revealed that a high frequency of watching pornographic films was associated with penetrative sexual experience, which is consistent with previous studies indicating that exposure to pornography may have harmful effects on sexual maturation and behaviours in adolescents [17, 68, 69] and that first sex was associated with exposure to pornography [7072]. In addition, another study involving adolescents aged 10-19 years in rural eastern Uganda found that watching sexually explicit films was associated with ever having sexual intercourse [73].…”
Section: Discussionsupporting
confidence: 90%
“…Paparan dini terhadap konten pornografi pada anak dan remaja dapat menyebabkan munculnya kenakalan remaja, perilaku seksual beresiko tinggi, serta penggunaan narkoba (Adarsh & Sahoo, 2023). Hasil penelitian yang dilakukan kepada anak usia sekolah dasar menunjukkan bahwa paparan konten pornografi pada usia anak-anak menyebabkan perubahan perilaku seksual anak, dimana anak memunculkan imajinasi untuk menyentuh bagian tubuh teman lawan jenisnya (Luthfiyatin et al, 2020).…”
Section: Latar Belakangunclassified
“…Pertemuan pertama ini diawali dengan sesi pembukaan dan perkenalan diri pemateri dan para peserta, penjelasan maksud dan tujuan kegiatan yang akan dilakukan, dan kemudian dilanjutkan dengan pengisian lembar pre-test untuk mengukur pengetahuan peserta sebelum diberikan psikoedukasi. Pada sesi psikoedukasi, materi yang disampaikan pada kegiatan ini ialah sebagai berikut:1) Dampak Buruk Pornografi dan Bentuk Pencegahan Kecanduan PornografiPornografi didefinisikan sebagai penggambaran sujek seksual yang digunakan dengan tujuan untuk membangkitkan Hasrat seksual yang umumnya berbentuk majalah, video, buku maupun video games(Adarsh & Sahoo, 2023). Pornografi menurut Undang-Undang No.…”
unclassified
“…Pornography could indeed be harmful [4]. All countries are concerned, and regulations in India have passed to protect teenagers, and porn sites have been banned [5]. However, few studies consider that pornography could be used for triggering sexual education of teenagers who could talk about sexual behaviors to parents or adults at home or at school [6,7].…”
Section: Introductionmentioning
confidence: 99%